Minimizing Energy consumption, Energy Poverty and Global and Local Climate Change in the Built Environment : Innovating to Zero : Casualties and Impacts in a Zero Concept World - Santamouris, Matthaios, author 635755 (Amsterdam : Elsevier, 2019)
Minimizing Energy Consumption, Energy Poverty and Global and Local Climate Change in the Built Environment: Innovating to Zero analyzes three major issues of the built environment, including the political, economic and technical contexts, the impacts of global and local climate change, and the technical and social characteristics of energy poverty. In addition, the book addresses the causes and reasons for the magnitude and characteristics of the built environment's energy consumption. Users will find a fresh view of energy consumption in the built environment, especially in relation to energy poverty and climate change from the ZERO energy world perspective.Presents and analyzes over twenty specific linkages and causalities between energy consumption, climate change and energy poverty Describes the state-of-the-art regarding the energy consumption of buildings in Europe and recent trends and characteristics Explores how can we transform problems into opportunitiesExamines how we can increase the added value of technological, economic and social interventions to generate wealth and offer employment opportunities.